Reviews of modern quantum chemistry : A celebration of the contributions of Robert G. Parr Volume I - Sen, K. D. (Singapore World Scientific, 2002)
This book presents state-of-the-art reviews covering nearly all major areas of modern quantum chemistry. It highlights advances in synthesis, structure, reactivity, and dynamics, emphasizing control and computational tools that bridge life and physical sciences. Featuring 59 in-depth reviews by leading scientists from 22 countries, it reflects the global progress in the field. With a foreword by Nobel laureate Walter Kohn, the volume honors Professor Robert G. Parr on his 80th birthday.
Includes bibliographical references and index
Keywords: Kỹ thuật công nghệ hoá học